SWOT analysis of Turkish Energy Market in the context of Electricity Market in the context of electricity market - Çelıkkol, Hakan; Köse, Fatma (Copernican Journal of Finance & Accounting, 2015)
Electricity energy is an indispendable part of life with continuously improving technology. Growth of the sector is unavoidable due to the increasing need of electricity. Properly functioning market structure is also important to attract investments in the sector. Therefore, plenty of steps are taken and essential changes are being done. Even though progress has been made in regards to the process that starting with the Electricity Market Law and aims to have an electricity market that is clear, reliable, competitive, and integrated with electricity markets of other countries, it has not yet reached this desired goal. Therefore, Turkish Energy Market was decided to establish the name of more liberal and more reliable electricity market. Only electricity trading is going to be done in this market at the first step. Purpose of the study is determining of potential changes in the market after Turkish Energy Market foundation. For this purpose, primarily current situation of electricity market is mentioned to understand changes that will happen in the market. Finally, weaknesses, strengths, threats and opportunities for electricity market are tried to specify by SWOT analysis.